Analisis Strategi Penjualan UMKM di Kabupaten Gianyar Menghadapi e-Commerce di Era Digital - Ayu Gede Willdahlia; Mila Rosa Desmayani; Wiwik Sri Rahayu; Daeka Cahyaningsih (Widya Manajemen, 2023)
This study aims to obtain the results of a sales strategy using SWOT analysis on MSMEs in Gianyar Regency in increasing sales of MSME products during the pandemic. Methods The research was carried out with descriptive qualitative methods where data collection was carried out by distributing questionnaires to respondents. Purposive Sampling. The results of this study found that in order to survive and increase sales during the pandemic, MSMEs in Gianyar Regency can take advantage of online Platforms (social media, websites), use attractive marketing strategies, develop urban style market segments, and provide training on the use of information technology for owners. SMEs. In order to increase the use of digital media to promote MSME products, training on the use of Wifi and other internet network providers was provided. Another thing that needs to be done is product innovation and taking advantage of the government's financial policy in the form of people's business loans to increase sales.